Human planet - British Broadcasting Corporation (U.S.A: British Broadcasting Corporation, 2011)
Human planet is an epic yet celebration of the amazing, complex, profound and sometimes challenging relationship between humankind and nature. Humans are the ultimate animals - the most successful species on the planet. From the frozen Arctic to steamy rainforests, from tiny islands in vast oceans to parched deserts, people have found remarkable ways to adapt and survive. We've done this by harnessing our immense courage and ingenuity; learning to live with and utilize the other creatures with which we share these wild places. Human Planet weaves together eighty inspiring stories, many never told before, set to a globally-influenced soundtrack by award-winning composer Nitin Sawhney. Each episode focuses on a particular habitat and reveals how its people have created astonishing solutions in the face of extreme adversity. Finally we visit the urban jungle, where most of us now live, and discover why the connection between humanity and nature here is the most vital of all.